Composite FRP reinforced concrete members with fiber reinforced polymer spirals. (October 2021) - Ali, Ahmed H.; Mohamed, Hamdy M.; Benmokrane, Brahim
Abstract: There is a limited design guidance for practitioners regarding the shear design equations of circular-concrete members with fiber reinforced polymer (FRP) reinforcements, especially the case of incorporating FRP bars and spirals. The objective of this study is to enhance the methods used for estimating the shear capacity of reinforced concrete (RC) beams with FRP bars and spirals. A database of 44 circular concrete beams reinforced with FRP bars tested under shear were compiled from different experimental studies. Two proposed models based on approaches developed for rectangular sections, to predict the shear capacity of beams without and with stirrups, were compared with the selected available shear design equations. The shear strength estimated using the proposed models are slightly more accurate. The comparison indicates that the shear capacity of FRP-reinforced concrete members with circular cross sections may be determined with the V cf and Vsf approaches developed for rectangular sections provided that certain modifications are made to take into account the effective shear depth, equivalent breadth, the mechanical properties and geometry of GFRP spirals.